EFFECTS OF CORTISOL ON CULTURED RAT HEART CELLS : Lipase Activity, Fatty Acid Oxidation, Glycogen Metabolism, and ATP Levels as Related to the Beating Phenomenon - Anastasia, J. V. (The Rockefeller University Press, 1973)
This paper reports the determination of the ability of rat heart cells in culture to release [(14)C]palmitate from its triglyceride and to oxidize this fatty acid and free [(14)C]palmitate to (14)CO(2) when the cells are actively beating and when they stop beating after aging in culture. In addition, the levels of glucose, glycogen, and ATP were determined to relate the concentration of these metabolites with beating and with cessation of beating. When young rat heart cells in culture are actively beating, they oxidize free fatty acids at a rate parallel with cellular ATP production. Both fatty acid oxidation and ATP production remain constant while the cells continue to beat. Furthermore, glucose is removed from the growth medium by the cells and stored as glycogen. When cultured cells stop beating, a decrease is seen in their ability to oxidize free fatty acids and to release them from their corresponding triglycerides. Concomitant with decreased fatty acid oxidation is a decrease in cellular levels of ATP until beating ceases. Midway between initiation of cultures and cessation of beating the cells begin to mobilize the stored glycogen. When the growth medium is supplemented with cortisol acetate and given to cultures which have ceased to beat, reinitiation of beating occurs. Furthermore, all decreases previously observed in ATP levels, fatty acid oxidation, and esterase activity are restored.